Pengaruh Penggunaan Media KIT terhadap Prestasi Belajar Peserta Didik - Annisa Nurul Azizah; Nana Suryana; Jonari Hanafi (Latifah Pres, 2021)
The use of KIT media is media that aims to develop students' learning achievement by using a tool that can make it easier for children to understand learning. Student achievement in grade VI SDN Tirtalaya tends to decrease. The formulation of the problem of this research is how the influence of the use of KIT media on student achievement in Natural Sciences Subjects in class VI SDN Tirtalaya. The aim is to find out how the influence of the use of KIT media on students' learning achievements in Natural Sciences Subjects in class VI SDN Tirtalaya. The research uses descriptive quantitative approach method. The study population was 118 respondents with a sample of 30 respondents, sampling using the purposive sampling technique. Data collection techniques using questionnaires and observation guidelines. Quantitative data processing is completed through descriptive data processing with Spearman rank correlation rs. Based on the results of data processing the use of KIT media on Natural Sciences subjects got an average count (x ̅) of 42, at an interval of 41-44, the use of KIT media on Natural Sciences subjects in class VI SDN Tirtalaya is good. Student achievement in grade VI SDN Tirtalaya got an average score (x ̅) 79 at an interval of 78-81 So the learning achievement of grade VI SDN Tirtalaya is low. The Influence of the Use of KIT Media on Student Learning Achievement in Natural Sciences Class VI SDN Tirtalaya has a positive and significant effect with sufficient classification, as evidenced by the rs value of 0.49 at intervals of 0.41 - 0.60, and the results from the calculation of tcount and ttable obtained a result of 2.974 then 2.048 Ha accepted H0 was rejected. Based on the results of this study, it is recommended for teachers to be able to carry out learning to the maximum, motivate and encourage students to interest in learning to increase, and students are advised to always sit in the front seat.